UJI DAYA HASIL BEBERAPA GALUR MENTIMUN HYBRIDA ( Cucumis sativus L ) di Bandung, Garut, Sumedang pada Musim Kemarau dan Penghujan - Uum Sumpena; Gungun Wiguna; Rossi Prabowo (Universitas Wahid Hasyim, 2016)
ABSTRACT Yield Trial of Cucumber Hybrid Lines at Bandung, Garut, Sumedang on Dry season and Wet season. The experiment was a series of activities to numbers of location and seasion of field trial for variety released. The experimental design was Randomized Complete Block Design with 4 replications and consisted of 40 plant per plot. The objective of the research was to find out high yielding of cucumber lines for Bandung, Garut, Sumedang at dry and wet season. The results obtained that Hybrid one washighest yielding (40.97 ton/ha) than check variety of Roberto (33.51 ton/ha). The cucumber of hybrid one were comparable to check variety of Misano (41.82 ton/ha) and Wulan (41.00 ton/ha). The cucumber Hybrid one were adapted at mid altitude of Districts Garut, Sumedang and Bandung. Keywords : cucumis sativus , hybrid lines, yield, location,season